Silicon-Mediated Adjustments in C:N:P Ratios for Improved Beetroot Yield under Ammonium-Induced Stress - Olivera-Viciedo, Dilier; Salas Aguilar, Daimy; de Mello Prado, Renato [UNESP]; Peña Calzada, Kolima; Calero Hurtado, Alexander; de Cássia Piccolo, Marisa; Bomfim Soares, Mariana [UNESP]; Lizcano Toledo, Rodolfo; Alves, Guilherme Ribeiro; Ferreira, Daniele; Rodrigues, Rosane; de Moura Zanine, Anderson (MDPI, 2024)
Nitrogen (N) holds a prominent position in the metabolic system of plants, as it is a main constituent of amino acids, which are the basic building blocks of proteins and enzymes. Plants primarily absorb N in the form of ammonium (NH4+) and nitrate (NO3−). However, most plants exhibit severe toxicity symptoms when exposed to NH4+ as the sole N source. Addressing NH4+ stress requires effective strategies, and the use of silicon (Si) has shown promising results. However, there is a lack of underlying studies on the impact of NH4+ toxicity on C:N:P stoichiometric balance and the role of Si in these ratios. In this study, we explored the effects of varying NH4+ concentrations (1, 7.5, 15, 22.5, and 30 mmol L−1) on the C:N:P stoichiometry and yield of beetroot in hydroponic conditions. Additionally, we investigated whether the application of Si (2 mmol L−1) could mitigate the detrimental effects caused by toxic NH4+ levels. The experiment followed a randomized block design based on a 5 × 2 factorial scheme with four replicates. Results revealed that in the presence of Si, both [N] and [P] significantly increased in shoots and roots, peaking at 15 mmol L−1 of NH4+ in the nutrient solution. While shoot [C] remained stable, root [C] increased with NH4+ concentrations of 22.5 and 30 mmol L−1, respectively. Moreover, shoot and root [Si] increased with higher NH4+ levels in the nutrient solution. The findings underscored homeostatic instability under the highest NH4+ levels, particularly in plants cultivated without Si in the nutritive solution, leading to a reduction in both shoot and root dry matter production.
Keywords: abiotic stress; ammonium toxicity; Beta vulgaris; C:N:P stoichiometry; hydroponic conditions; nitrogen assimilation; nutrient balance; phosphorus uptake; plant growth; silicon application